Training and pilot implementation of the World Health Organization’s caregiver skills training program in Egypt - Dababnah, Sarah; Ibrahim, Alaa T.; Yusuf, Afiqah; Gaber, Eman; Elshafey, Hadeer; Kotb, Heba W.; Elsabbagh, Mayada; Ramzy, Sherine; Eskander, Stephanie; Theis, Andrea; Elsherif, Aya; Dixon, Pamela (Research in Autism, 2025)
There are numerous challenges in the Eastern Mediterranean Region to access timely and appropriate autism-related care. The small body of research in Egypt finds a dearth of adequately trained professionals and services for young autistic children and their caregivers. This brief report summarizes efforts to engage local and global partners to train Egyptian professionals to deliver the World Health Organization’s Caregiver Skills Training program, a caregiver-mediated intervention (nine group and three individual sessions) designed explicitly to fill in the global gap of autism services. We used qualitative and quantitative methods to assess local professionals’ perspectives on the intervention, the implementation climate, intervention delivery, and future training of non-specialists. We trained 16 full-time public health employees on the intervention, who reported on their confidence to deliver the intervention, strategies to train non-specialists, and knowledge of which children would benefit. They also reported on potential barriers implementing the intervention. Our research underscored the value of having a range of local and global partners to collectively address provider and intervention shortages in resource-limited countries. •Services are limited for children with autism and their families in Egypt.•Egyptian and global partners trained providers on the WHO Caregiver Skills Training program.•Providers felt confident using the program for parents of young autistic children.•Global and local partners can work together to address resource limitations.